The Effect of Sexual Abuse on Self-esteem Among Adolescents: The Impact of Gender, Parental Support and Type of Perpetrator - Íris Hildur Birgisdóttir 1990- (2016)
There is a great need to recognize the adverse effects childhood sexual abuse can have on individuals and the various factors that may interact with these effects. This study focuses on the effect that sexual abuse can have on self-esteem of adolescents, with regard to gender, parental support and type of perpetrator (i.e. intra- or extrafamilial abusers). The sample in this study consists of Icelandic adolescents who participated in a study called Youth in Iceland 2004, which was conducted in all Icelandic secondary schools. In accordance with the literature the following hypotheses were tested: Those who have been intrafamilially sexually abused will have lower self-esteem than those extrafamilially sexually abused, boys who have been sexually abused will have better self-esteem than girls who have been sexually abused and those who have been sexually abused and have high support from their parents will have a higher self-esteem than those who have been sexually abused and have low support from their parents. The results revealed significant main effects for sexual abuse; those who had not been sexually abused had higher self-esteem than those that were sexually abused. But the difference between intra- and extrafamilial abuse was not significant. There were significant main effects for gender; boys had better self-esteem than girls. There were also significant main effects for support from parents; those who had higher support from their parents had higher self-esteem than those who had low support from their parents. There was not a significant interaction between any of the variables. Það er mikil þörf fyrir því að bera kennsl á þau skaðlegu áhrif sem kynferðisleg misnotkun hefur á einstaklinga og hina ýmsu þætti sem geta haft áhrif þar á. Þessi rannsókn einblínir á þau áhrif sem kynferðislegt ofbeldi hefur á sjálfstraust hjá unglingum með tilliti til kyns, stuðnings frá foreldrum og tegund geranda (innan- utan fjölskyldunnar). Úrtakið í rannsókninni samanstóð af íslenskum unglingum sem tóku þátt í ...